Genetic Background for Development of Resistance Mutations within the HCV Ns3 Protease–Helicase in Direct Acting Antiviral Naive Patients. Issue 5 (July 2014) - Grammatikos, Georgios; Jabara, Cassandra B; Ahmad, Monazza Q; Herrmann, Eva; Zeuzem, Stefan; Welsch, Christoph
Background: Subtype-specific response to ketoamide NS3 protease inhibitors is observed in patients with genotype 1 HCV infection. Whether the genetic diversity in the molecular target site of ketoamide compounds prior to treatment plays a role for resistance development and lower treatment response in subtype 1a is poorly understood. Methods: Using a public database, we retrieved worldwide NS3-sequence information of 581 dominant HCV variants from patients chronically infected with genotype 1 that were naive to direct-acting antivirals. We applied measures from phylogeny to study the pretreatment genetic diversity and complexity in NS3 full-length as well as the protease–helicase interface for subtype 1a and 1b, respectively. Results: We found polymorphic sites more frequently in variants of subtype 1b than subtype 1a. Moreover, a significantly higher number of synonymous and non-synonymous substitutions were found in subtype 1b ( P <0.001). Transitions were more frequent than transversions, most notably in subtype 1a, whereas the higher average number of nucleotide differences per site was found in subtype 1b. A comparison of NS3 full-length versus domain interface residues for both subtypes revealed a significant difference only for synonymous substitutions ( P <0.001). Conclusions: Our study suggests that the nature of a mismatch nucleotide exchange in NS3 may constitute an important viral genetic factor for response to ketoamide protease inhibitors. Our analysis further suggests that the subtype-specific pace of resistance development seen in clinical trials is not primarily related to differences in genetic diversity in the direct acting antiviral naive population, but rather appears to correlate with the natural frequency of transition mutations characteristic of each subtype.